2019
DOI: 10.1002/art.40863
|View full text |Cite
|
Sign up to set email alerts
|

Pim‐1 as a Therapeutic Target in Lupus Nephritis

Abstract: Objective Lupus nephritis (LN) is a major determinant of morbidity and mortality in systemic lupus erythematosus (SLE). Pim‐1 regulates lymphocyte proliferation and activation. The role of Pim‐1 in autoimmune disease remains unclear. This study was undertaken to test the hypothesis that inhibition of Pim‐1 would have therapeutic potential in patients with LN. Methods Pim‐1 expression was analyzed in lupus‐prone (NZB × NZW)F1 mice (n = 6), human peripheral blood mononuclear cells (PBMCs) from SLE patients (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 49 publications
1
25
0
1
Order By: Relevance
“…In lupus-prone mice, inhibition of NLRP3 with MCC950 ameliorated proteinuria and renal histologic lesions [102]. Fu et.al also demonstrated that NZB/W F1 mice treated with pim-1 inhibitor AZD1208 showed a suppression of NLRP3 inflammasome activation and a significant reduction in the severity of lupus nephritis [108]. The expression of AIM2, another inflammasome sensing double-stranded nucleic acids in the cytoplasm, was positively correlated with disease severity in patients with SLE and lupus-prone mouse model.…”
Section: Pyroptosismentioning
confidence: 99%
“…In lupus-prone mice, inhibition of NLRP3 with MCC950 ameliorated proteinuria and renal histologic lesions [102]. Fu et.al also demonstrated that NZB/W F1 mice treated with pim-1 inhibitor AZD1208 showed a suppression of NLRP3 inflammasome activation and a significant reduction in the severity of lupus nephritis [108]. The expression of AIM2, another inflammasome sensing double-stranded nucleic acids in the cytoplasm, was positively correlated with disease severity in patients with SLE and lupus-prone mouse model.…”
Section: Pyroptosismentioning
confidence: 99%
“…Overexpression of PIM1 appears to influence cancer development in three ways; preventing apoptosis, enhancing cellular proliferation and through promoting genomic instability (75). More specific to kidney research, PIM1 is aberrantly overexpressed in renal cell carcinoma (76) and lupus nephritis (77). In this analysis we identified top-ranked dmCpGs present within the 3' UTR and north shore of PIM1 which resulted in an increase in the FC in individuals with T1D-ESKD.…”
Section: Discussionmentioning
confidence: 96%
“…Functionally, studies have well proven that the 34 kDa Pim1 plays a crucial role in a wide range of cell processes and diseases, such as cell proliferation, apoptosis, mitochondrial integrity, cellular senescence, myocardial injury, lupus nephritis and Alzheimer's disease through interaction, stabilization, and phosphorylation of many downstream targets 29,[31][32][33][34][35][36][37][38] . Importantly, as a direct target gene of JAK/STAT-signaling pathway 21,39,40 , Pim1 kinase is also involved in immune regulation and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%